2019
DOI: 10.1101/800771
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Platelets fuel the inflammasome activation of innate immune cells

Abstract: ABSTRACTThe inflammasomes control the bioactivity of pro-inflammatory cytokines of the interleukin (IL)-1 family. The inflammasome assembled by NLRP3 has been predominantly studied in homogenous cell populations in vitro, neglecting the influence of cellular interactions that occur in vivo. Here, we show that platelets, the second most abundant cells in the blood, boost the inflammasome capacity of human macrophages and neutrophils, and are critical for IL-1 production by monoc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 98 publications
(125 reference statements)
3
45
0
1
Order By: Relevance
“…HGF exerts potent anti-inflammatory effects, which seem to involve a signaling cascade leading to increased expression of IL-1Ra [37]. In agreement with the upregulation of IL-1Ra in thrombocytopenic patients, we recently demonstrated that low platelet counts in Pv malaria are associated with a progressive decrease in plasma concentrations of IL-1β [19]. While IL-1Ra in Pv infections has been little explored, elevated IL-1Ra levels have been associated with increased disease severity in P. falciparum malaria-infected children [38].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…HGF exerts potent anti-inflammatory effects, which seem to involve a signaling cascade leading to increased expression of IL-1Ra [37]. In agreement with the upregulation of IL-1Ra in thrombocytopenic patients, we recently demonstrated that low platelet counts in Pv malaria are associated with a progressive decrease in plasma concentrations of IL-1β [19]. While IL-1Ra in Pv infections has been little explored, elevated IL-1Ra levels have been associated with increased disease severity in P. falciparum malaria-infected children [38].…”
Section: Discussionsupporting
confidence: 54%
“…Growing evidence strengthen an essential role of platelets as mediators of inflammation through their capacity to secrete numerous proteins upon activation or via their interaction with the endothelium, or with leukocytes [18]. For example, we have recently demonstrated that platelets enhance the inflammasome activity of innate immune cells and amplify IL-1-driven inflammation [19]. Therefore, it is possible to 4 speculate that platelets may be critical players in Pv-mediated systemic inflammatory response.…”
Section: Introductionmentioning
confidence: 96%
“…Endothelial-associated vWF putatively plays a role in atherogenesis by recruiting platelets to vascular surface. There are many mechanisms by which platelets can promote plaque activation, particularly through vascular inflammatory activation, oxidative capacity, and direct activation of the inflammasome complex ( 2 , 29 , 30 ). Platelet-derived secreted factors such as chemokines (C-C and C-X-C motif), interleukins (IL-1b, IL-8), and CD40L all have been implicated as contributors to thrombo-inflammation, and many of which contribute to up-regulation of NFκB ( 3 , 4 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that platelet activation is mediated by ROS-driven in ammasome activation [8]. In addition, NLRP3 are licensed by platelets to activate innate in ammasomes in immune cells, and platelet amount is positively correlated with IL-1β in plasma [9]. It suggests that targeting oxidative stress and platelet activation inhibition may promote the inhibition of pyroptosis in cerebral ischemia to reduce cell death and promote functional recover.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that hemoglobin induced platelet activation is mediated by ROS-driven proteasome activity and in ammasome activation [8]. In addition, platelets license NLRP3 to activate in ammasomes in innate immune cells and shape IL-1β at the same time, whose count is associated with IL-1β in plasma [9].These results suggest that targeted oxidative stress and platelet activation inhibition may promote the down-regulation of pyroptosis in cerebral ischemia and become a new therapeutic strategy for cerebral ischemia.…”
Section: Introductionmentioning
confidence: 99%